An implementation of Bay’ Al- Dayn Bi Al Sila’ in Malaysia - Nor Amirah, Shaari (2021)
The issue of selling debt is a controversial sale contract in many of its implementation due to the subject matter of the contract. Bai al dayn contract is not widely implement by the other Islamic banks especially in Middle East countries beside Malaysia due to the issues that the sale of debt has been sell at discount price, and debt cannot be considered as asset. Furthermore, there are very few researches been done related to Bay’ Al-Dayn and Bay’ Al-Dayn Bi Al-Sila’’s (BDBS) contract. Therefore, this study attempt to investigate and explore the issues and challenges in implementing BDBS from practitioner’s, expert’s, and client's perspective and the goal is to show process flow of BDBS current implementation in Malaysia. The research design used in this study is qualitative approach through in-depth interview. Several sets of open-ended questionnaires have been developed and interviews were conducted and analyzed using content analysis based themes. In-depth interview has been done with nine (9) informants who involve indirectly with the contract. The informants that involved in this study including four practitioners from industrial practitioners, two informants are experts or scholars, and another three informants are clients. Based on the interview, most of the informants agree on the enhancement of the new contracts. However, to change into the new system, many challenges and impact have to be considered especially on cost, staff training and more documentation needed on the new process. These impacts affect the practitioner more rather than the clients itself where as industrial practitioners they have to ensure the changes made align with shariah compliance requirement. The implication of this study is the sale and purchase of the commodities from BDBS contract is indirectly help the cycle of economies in our country. This also could help small and medium entrepreneur to explore more on the shariah compliance financing facilities and other Islamic product which more suitable and ready to be used.